Internal Auditor’s Performance In Sas Parts Companies - Fiki Hidayat; Kun Ismawati; Kunreza Oktaviansyah (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
Auditors’s performance currently faces challenges in gaining public trust. Many factors are considered to influence, while several previous studies still show inconsistent results. The aim of the research is to identify the influence of independence, worksexperience and ethics’s code on performance of internal auditors at SAS PARTS companies. This quantitative research’s data gained from questionnaires. The research’s population were 40 auditors spread across branch offices in Indonesia. The saturation sampling techniques used in this research. The method to analyze data was multiple linear regression. Indications of the research’s results as follows: 1. Independence does not affect internal auditor’s performance. It can be shown from the third question item which states that the lack of auditee assistance in collecting audit evidence has an impact on auditor performance. Auditor performance is not solely shown by auditor independence. 2. Work experience does not influence internal auditor’s performance, this is because the majority of respondents work less than 3 years which causes their lack on experience in carrying-out assignments. 3. The Ethic’s code affects the performance of internal auditor because of the existence of a code of ethics as a guide for the auditor to know what is allowed and not to be done, in order to improve the internal auditor’s performance. 4. Independence, work experience, and code of ethics simultaneously (together) affect the performance of auditors at SAS PARTS Company. There has never been any other previous research on this research object of SAS PARTS Company about internal auditor’s performance.